INCIDENTAL FINDINGS OF POLYPOID CYSTITIS IN A 6-YEAR OLD CHILD WITHOUT ANY HISTORY OF LOWER URINARY TRACT SYMPTOMS AND PREVIOUS URINARY CATHETERIZATION - Masood, Basit; Iqbal, Waqas; Iqbal, Nadeem; Hussain, Ijaz; Ul Haq, Anwar; Rehman, Usama; Haroon, Asna; Khan, Faheemullah; Iqbal, Daud; Hasan, Aisha (Journal of Ayub Medical College Abbottabad, 2020)
A 6-year-old boy presented to ER with acute pain in right iliac fossa without any history of lower urinary tract symptoms, haematuria and urinary catheterization. Ultrasound showed loculated cystic area in pelvis with non-visualized appendix. A CT scan abdomen and pelvis revealed loculated, multi-septated cystic lesion in right hemipelvis thought to be a collection from possible appendicular inflammation / perforation. The laboratory findings revealed raised CRP and normal urine routine examination and culture. Exploratory laparotomy revealed cystic urinary bladder growth involving dome with normal appendix, partial cystectomy was done. Histopathology confirmed polypoid cystitis with no evidence of malignancy. This is a very rare presentation of polypoidal cystitis, not previously reported in literature.